L’accroissement naturel de la population catholique québécoise avant 1850 : aperçus historiographiques et quantitatifs - Ouellet, Fernand (L'Actualité économique, 1983)
AbstractThe author presents a critical evaluation of the different estimates of birth, death, and marriage rates in French Canada before 1850. He examines critically the sensitivity of these estimates to changes in the nature of the prevailing conceptual framework. In particular, the impact of the 'natalist' tradition and of the 'demographic transition hypothesis' on these estimates is noted.